2014
DOI: 10.1371/journal.pone.0089458
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Socioeconomic Risk Factors Associated with Probable Resistance to Ceftriaxone and Resistance to Penicillin and Tetracycline in Neisseria gonorrhoeae in Shanghai

Abstract: Globally, incidence of Neisseria gonorrhoeae infection is once again the highest of the bacterial sexually transmitted infections. The bacterium can produce serious complications in those infected, and emerging resistance to third generation cephalosporins could usher in an era of potentially untreatable gonorrhea. This research aimed to identify risk factors for antibiotic resistant gonorrhea infection among clients at a Shanghai sexually transmitted infection clinic over two time periods, 2004–2005 and 2008–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
1
24
4
1
Order By: Relevance
“…Like Trecker et al [ 44 ] and McLean et al [ 45 ] but in contrast to Town et al [ 46 ], our study showed a significant association with age: for heterosexual men, being older than 25 years of age was significantly associated with resistance to azithromycin and being older than 35 years of age was associated with decreased susceptibility to ceftriaxone. We also found a significant association with a higher number of sex partners (3–5 partners) and resistance to azithromycin among heterosexual men.…”
Section: Discussioncontrasting
confidence: 57%
“…Like Trecker et al [ 44 ] and McLean et al [ 45 ] but in contrast to Town et al [ 46 ], our study showed a significant association with age: for heterosexual men, being older than 25 years of age was significantly associated with resistance to azithromycin and being older than 35 years of age was associated with decreased susceptibility to ceftriaxone. We also found a significant association with a higher number of sex partners (3–5 partners) and resistance to azithromycin among heterosexual men.…”
Section: Discussioncontrasting
confidence: 57%
“…The public health burden of N. gonorrhoeae infections is heightened due to continued high rates of resistance to previously used antimicrobials including fluoroquinolones. High rates of ciprofloxacin resistance have been reported from different parts of the world and more recently from Shanghai 16 . Our region itself has reported high rates (83.3%) in 2008 17 and 94 per cent thereafter 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In Nanjing, China, PPNG and TRNG were reported to increase from 8.0 to 44.4 % and from 1.8 to 32.8 % respectively during 1999–2006 [ 31 ]. A high PPNG prevalence of 51.3 and 49.2 % were maintained while a TRNG increased from 19.6 to 42.1 % was observed in the neighboring city of Shanghai over two time periods, 2004–2005 and 2008–2011 [ 32 ]. In Guangzhou, the prevalence of PPNG increased yearly from 2 to 21.8 % and TRNG from 1.5 to 27.2 % during 1996–2001 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%